The Effect of Applying Contextual Teaching and Learning in Problem-Based Learning on Students’ Critical Thinking Skills in Chemical Equilibrium - Fadillah Desintha Yuliani; Harjito (Chemistry in Education, 2026)
Critical thinking skills are essential 21st-century skills that need to be developed, including in complex chemistry equilibrium material that requires in-depth analysis. Context-based learning and problem solving, such as a combination of Problem Based Learning (PBL) and Contextual Teaching and Learning (CTL), are expected to combine the strengths of both in improving critical thinking skills. This study aims to analyze the effect of applying PBL-CTL on critical thinking skills and compare it with non-CTL PBL. The type of research is a quasi-experiment – post-test non-equivalent control group design. The sample selection was conducted using a combination of purposive sampling and cluster random sampling after testing the normality and equality of variance in the population. This study was conducted by comparing two sample groups. The experimental group applied PBL-CTL, while the control group used PBL. Data were obtained from the completion of worksheets, post-tests, and observations. The Mann-Whitney U test results showed significant differences in critical thinking skills (p=0.010) and knowledge (p=0.038), with the experimental group having a higher mean rank. The effect size test indicated a moderate effect on critical thinking skills (r=0.304) and knowledge (r=0.244). These findings prove that PBL-CTL has a significant moderate effect on improving students' critical thinking skills and knowledge in chemical equilibrium material, with a greater effect on critical thinking skills. In addition, students in the PBL-CTL group consistently achieved higher scores on critical thinking indicators and mastery of material compared to the non-CTL PBL group.